Elevated blood eosinophils in early infancy are predictive of atopic dermatitis in children with risk for atopy. Issue 7 (9th August 2016) - Rossberg, Siri; Gerhold, Kerstin; Geske, Thomas; Zimmermann, Kurt; Menke, Georg; Zaino, Mohammad; Wahn, Ulrich; Hamelmann, Eckard; Lau, Susanne
Abstract: Background: Accessible markers to predict the development of atopic diseases are highly desirable but yet matter of debate. Objective: We investigated the role of blood eosinophils at 4 weeks and 7 months of life and their association with developing atopic dermatitis (AD) in a birth cohort of children with atopic heredity. Methods: Infant blood samples for eosinophil counts were taken from 559 infants at 4 weeks and from 467 infants at 7 month of life with at least one atopic parent. Elevation of blood eosinophils was defined as ≥ 5% of total leukocytes and the asscociation for the occurrence of AD was assessed by entering 2 × 2 tables and the odds ratios were estimated followed by hypothesis testing against the alternate working hypothesis: odds ratio < > 1. Survival analysis was carried out estimating the Kaplan‐Meier product limit estimator from the life‐time table of AD score and time to AD manifestation stratified by the eosinophil binary score. Results: Elevated blood eosinophils observed at 4 weeks were significantly associated with the occurrence of AD in the whole cohort at the age of 7 months (p = 0.007), 1 year (p = 0.004), 2 years (p = 0.007) and 3 years (p = 0.006) of life. AD occurred app. 12 weeks earlier in infants with elevated blood eosinophils at 4 weeks of life. Blood eosinophil counts ≥5% at 7 months of life failed to show significance for AD; for eosinophils at 4.5% a significant association at 7 months (p = 0.005), and 1 year of life (p = 0.039), 2 years (p = 0.033) and 3 years (p = 0.034) was observed. Conclusion: Elevated blood eosinophils at age 4 weeks have a predictive value for the onset of atopic dermatitis in infancy and early childhood in children with high risk for atopy. Early eosinophil counts may therefore be helpful for counseling parents to provide infant skincare but furthermore identify individuals for interventional trials aiming at allergy prevention.